2006
DOI: 10.1074/jbc.m607714200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Specific Serine Residues in the PKR Activation Domain of PACT Is Essential for Its Ability to Mediate Apoptosis

Abstract: Activation of the latent protein kinase, PKR, by extracellular stresses and triggering of resultant cellular apoptosis are mediated by the protein, PACT, which itself gets phosphorylated in stressed cells. We have analyzed the underlying biochemical mechanism by carrying out alanine-scanning mutagenesis of the PKR activation domain of PACT. Among the indispensable residues identified were two serine residues, whose phosphorylation was essential for the cellular actions of PACT. Two-dimensional gel analysis, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 28 publications
6
62
0
1
Order By: Relevance
“…[24][25][26][27][28] or activation of RNA-dependent protein kinase (PKR; refs. [29][30][31][32][33]. Alternatively, aptamer binding may modify some signaling pathways in MDSCs affecting their survival.…”
Section: Il4ra Mediates a Prosurvival Signaling In Mdscsmentioning
confidence: 99%
“…[24][25][26][27][28] or activation of RNA-dependent protein kinase (PKR; refs. [29][30][31][32][33]. Alternatively, aptamer binding may modify some signaling pathways in MDSCs affecting their survival.…”
Section: Il4ra Mediates a Prosurvival Signaling In Mdscsmentioning
confidence: 99%
“…Recently we showed that cellular stress signals cause PACT to dissociate from TRBP leading to PACT-mediated PKR activation. TRBP-PACT heterodimers present in unstressed cells dissociate, as PACT is phosphorylated on Ser-287 in M3 in response to oxidative stress, serum starvation, and endoplasmic reticulum (ER) stress (20,21) by a protein kinase yet to be identified. Stress-induced phosphorylation at serine 287 has a dual role in PACT-mediated PKR activation as it causes dissociation of the PACT-TRBP complex and at the same time increases PACT affinity for PKR (21).…”
mentioning
confidence: 99%
“…A hallmark of PACT function is its ability to activate PKR in the absence of dsRNA, suggesting PACT has virus-independent cellular roles (6). The dsRBMs of PACT, domains 1 and 2, mediate strong interaction with the 2 dsRBMs of PKR, but the ability to activate PKR is imparted by a third domain of PACT that binds to the PKR kinase domain (7)(8)(9). Binding of domain 3 causes PKR autophosphorylation by disrupting an intramolecular interaction within PKR that is responsible for keeping PKR in an inactive conformation (10).…”
mentioning
confidence: 99%
“…Binding of domain 3 causes PKR autophosphorylation by disrupting an intramolecular interaction within PKR that is responsible for keeping PKR in an inactive conformation (10). In mammalian cells, PACT itself is phosphorylated by treatment with various chemical stresses or growth factor withdrawal, allowing it to associate with PKR with increased affinity (7,9,11,12).…”
mentioning
confidence: 99%